Study on biotransformation and absorption of genistin based on fecal microbiota and Caco-2 cell - Li, Zhe; Wang, Yuqing; Wang, Zicheng; Wu, Dongxue; Zhao, Yuhao; Gong, Xun; Jiang, Quan; Xia, Congmin (Frontiers in Pharmacology, 2024)
Genistin, as a kind of natural isoflavone glycoside, has good biological activity, and its weak absorption makes it closely related to intestinal flora. However, the role of the intestinal flora is still unclear and whether the metabolites produced by the intestinal flora are absorbed systemically is also variable. Genistin was fermented for 24 h based on fecal bacteria fermentation technology. The components were qualitatively and quantitatively analyzed by HPLC and UHPLC-Q-Exactive Orbitrap Mass spectrometry. The composition of intestinal flora in fermentation samples from fecal bacteria was detected by 16S rRNA sequencing. Five representative probiotics were cultured in vitro and fermented with genistin to determine similarities and differences in genistin metabolites by different bacteria at different times. Finally, the absorption results of metabolites by fermentation were verified by a Caco-2 cell monolayer. The HPLC results of fecal fermentation showed that genistein levels increased from 0.0139±0.0057 mg/mL to 0.0426±0.0251 mg/mL and two new metabolites were produced. A total of 46 metabolites following fecal fermentation were identified, resulting from various biotransformation reaction products, such as decarbonylation, hydroxylation, and methylation. Simultaneously, the 16S rRNA results showed that the intestinal flora changed significantly before and after fermentation and that the intestinal microorganisms in the control (Con) group and the fermentation (Fer) group showed a significant separation trend. Five genera, Lactobacillus, Bifidobacterium, Parabacteroides, Sutterella, and Dorea, were considered the dominant flora for genistin fermentation. The qualitative results of fermentation of genistin by five probiotics at different times showed that there were significant differences in small molecule metabolites by fermentation of different bacteria. Meanwhile, most metabolites could be identified following fecal bacteria fermentation, which verified the importance of the dominant bacteria in the feces for the biotransformation of components. Finally, the absorption results of the metabolites based on the Caco-2 cell monolayer showed that 14 metabolites could be absorbed into the circulation in vivo through the mesentery. The small-molecule metabolites of genistin by fermentation of fecal bacteria can be well absorbed systemically by the